2004
DOI: 10.1093/jhered/esh082
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Species Amplification of Bovidae Microsatellites and Low Diversity of the Endangered Korean Goral

Abstract: The Korean goral (Nemorhaedus caudatus) is an endangered species of wild goat. The conservation and management of this species could benefit from a better understanding of its genetic diversity and structure. Cross-species amplification of 34 Bovidae microsatellite loci was tested on a panel of 6 Korean gorals and 10 domestic goats. After polymerase chain reaction (PCR) optimization, 29 (85.3%) microsatellite loci amplified successfully for the Korean gorals and 27 (79.4%) for the domestic goats. Of the amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 28 publications
2
21
1
2
Order By: Relevance
“…species ranged from 16.23 to 62.89% (Moore et al 1991;Kemp et al 1995;Fields and Scribner 1997;Baratti et al 2001;Kayang et al 2002;Reed et al 2003;Kim et al 2004). Studies show that it was difficult to screen microsatellite markers for duck by cross-species amplification from chicken loci (Huang et al 2005).…”
Section: Tablementioning
confidence: 99%
“…species ranged from 16.23 to 62.89% (Moore et al 1991;Kemp et al 1995;Fields and Scribner 1997;Baratti et al 2001;Kayang et al 2002;Reed et al 2003;Kim et al 2004). Studies show that it was difficult to screen microsatellite markers for duck by cross-species amplification from chicken loci (Huang et al 2005).…”
Section: Tablementioning
confidence: 99%
“…Since the genetic diversity of Korean goral populations is decreasing (Kim et al, 2004a), there is an urgent need to develop conservation projects to promote the recovery of both population size and distribution. Knowledge of the species' taxonomic status and population genetic structure is fundamental to developing effective strategies to this end (Lorenzini et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Min et al (2004) confirmed the phylogenetic relationship between long-tailed gorals and Japanese serows using partial mitochondrial DNA sequence, and also revealed that a Korean goral population is genetically closer to Russian than to Chinese populations. Kim et al (2004a) screened 34 Bovidae microsatellite markers through cross-species amplification of N. caudatus, and noted that the Korean goral population has the lowest level of heterozygosity among the Caprinae subfamily including goats, Alpine ibex and Spanish ibex. Additionally, An et al (2005) characterized 15 goral-specific microsatellite loci, and Kim et al (2008) reported molecular methods for species identification and sex determination for ungulate species of Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Мультиплексные панели микроса-теллитных маркеров, разработанные для домашних животных, могут быть с успехом использованы для оценки их диких сородичей [9,10]. В ряде иссле-дований было подтверждено, что гетерологичные микросателлиты домашне-го крупного рогатого скота (Bos taurus) могут применяться для характеристи-ки популяционной структуры и генеалогических связей различных видов трибы быков (Bovini) [11][12][13][14]. Так, 117 из 131 STR-маркера (94,3 %) оказались полиморфны у 10 особей домашнего яка (Poephagus grunniens) [12], у 11 осо-бей гаура 117 из 130 STR были кросс-амплифицированы (Bos gaurus) и 68 ло-кусов (58,1 %) оказались полиморфны [13].…”
unclassified
“…Так, 117 из 131 STR-маркера (94,3 %) оказались полиморфны у 10 особей домашнего яка (Poephagus grunniens) [12], у 11 осо-бей гаура 117 из 130 STR были кросс-амплифицированы (Bos gaurus) и 68 ло-кусов (58,1 %) оказались полиморфны [13]. Исследование 34 STR у 6 горалов (Nemorhaedus caudatus) позволило успешно амплифицировать 29 локусов, из которых 16 (55,2 %) оказались полиморфными [11].…”
unclassified